The Use of Tiktok Application in Geography Learning Based on Project-Based Learning in Improving Students’ Creative Thinking Skills in Public High School 16 Bandar Lampung - Deagustami, Raysa; Sinaga, Risma M.; Pujiati, Pujiati (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to explore the use of TikTok application as a learning media in improving students’ creative thinking skills at SMA Negeri 16 Bandar Lampung, especially in geography subject. The phenomenon that occurs shows that learning in high schools still focuses on basic thinking skills, so a more innovative approach is needed to develop higher-level thinking skills. Through qualitative research methods, data was collected from interviews with students and document analysis. The results show that the use of TikTok can attract students’ interest and provide a fun learning experience, thus encouraging them to more actively seek information and understand the material, especially regarding the dynamics of the lithosphere. In addition, project-based learning integrated with social media is proven effective in honing students’ creative thinking skills, including aspects of fluency, flexibility, originality, and elaboration. This research recommends the application of more varied and creative learning methods to improve the quality of education in the digital era.